Periodontitis and Porphyromonas gingivalis in Patients With Rheumatoid Arthritis. Issue 5 (May 2014) - Mikuls, Ted R.; Payne, Jeffrey B.; Yu, Fang; Thiele, Geoffrey M.; Reynolds, Richard J.; Cannon, Grant W.; Markt, Jeffrey; McGowan, David; Kerr, Gail S.; Redman, Robert S.; Reimold, Andreas; Griffiths, Garth; et al.
<x xml:space="preserve">Abstract</x> Objective To examine the degree to which shared risk factors explain the relationship of periodontitis (PD) to rheumatoid arthritis (RA) and to determine the associations of PD and Porphyromonas gingivalis with pathologic and clinical features of RA. Methods Patients with RA (n = 287) and patients with osteoarthritis as disease controls (n = 330) underwent a standardized periodontal examination. The HLA–DRB1 status of all participants was imputed using single‐nucleotide polymorphisms from the extended major histocompatibility complex. Circulating anti–P gingivalis antibodies were measured using an enzyme‐linked immunosorbent assay, and subgingival plaque was assessed for the presence of P gingivalis using polymerase chain reaction (PCR). Associations of PD with RA were examined using multivariable regression. Results Presence of PD was more common in patients with RA and patients with anti–citrullinated protein antibody (ACPA)–positive RA (n = 240; determined using the anti–cyclic citrullinated peptide 2 [anti–CCP‐2] test) than in controls (35% and 37%, respectively, versus 26%; P = 0.022 and P = 0.006, respectively). There were no differences between RA patients and controls in the levels of anti–P gingivalis or the frequency of P gingivalis positivity by PCR. The anti–P gingivalis findings showed a weak, but statistically significant, association with the findings for both anti–CCP‐2 (r = 0.14, P = 0.022) and rheumatoid factor (RF) (r = 0.19, P = 0.001). Presence of PD was associated with increased swollen joint counts (P = 0.004), greater disease activity according to the 28‐joint Disease Activity Score using C‐reactive protein level (P = 0.045), and higher total Sharp scores of radiographic damage (P = 0.015), as well as with the presence and levels of anti–CCP‐2 (P = 0.011) and RF (P < 0.001). The expression levels of select ACPAs (including antibodies to citrullinated filaggrin) were higher in patients with subgingival P gingivalis and in those with higher levels of anti–P gingivalis antibodies, irrespective of smoking status. Associations of PD with established seropositive RA were independent of all covariates examined, including evidence of P gingivalis infection. Conclusion Both PD and P gingivalis appear to shape the autoreactivity of RA. In addition, these results demonstrate an independent relationship between PD and established seropositive RA.